Association of Astigmatism with Allergic Conjunctivitis - Naseer, Muhammad Saad; Parveen, Shagufta; Muhammad Jahanzaib; Ahmad Khan, Fawad; Sajjad, Sania; Zahra, Syeda Muniba (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the association of astigmatism with allergic conjunctivitis.Study Design: Prospective observational study.Place and Duration of Study:  Armed Forces Institute of Ophthalmology, Jun to Dec 2023.Methodology: The study had 359 patients, and convenience sampling was performed. Baseline data was collected related to demographic characteristics, past medical history and co-morbidities. Allergic Conjunctivitis was diagnosed through examination with a slit-lamp. Astigmatism was diagnosed by measuring the refractive power of both eyes using an Automated Kerato Refractometer. Patients were pre-evaluated for Astigmatism and they were followed for period of 6 month. And post evaluated after 3 weeks, 3 months and 6 months. Data was collected, entered and analyzed in SPSS version 26.0. Chi Square test was applied and p